A DNA-based Archival Storage System - Bornholt, James; Lopez, Randolph; Carmean, Doug; Ceze, Luis; Seelig, Georg; Strauss, Karin (ASPLOS 2016 (International Conference on Architectural Support for Programming Languages and Operating Systems) - to appear, 2016)
Demand for data storage is growing exponentially, but the capacity of existing storage media is not keeping up. Using DNA to archive data is an attractive possibility because it is extremely dense, with a raw limit of 1 exabyte per cubic millimeter, and long-lasting, with observed half-life of over 500 years. This paper presents an architecture for a DNA-backed archival storage system. It is structured as a key-value store, and leverages common biochemical techniques to provide random access. We also propose a new encoding scheme that offers controllable redundancy, trading off reliability for density.